POSSIBILITIES OF PRODUCTION MANAGEMENT IN MANUFACTURING ENTERPRISE WITH ADVANCED METHODS - Majercak, Peter; Majercakova, Eva (Doprava a spoje, 2012)
The paper deals with a very hot topic and progressive methods of production management in the enterprise. The authors describe very precisely the traditional methods of production management in enterprises and system PUSH and PULL. Conclusion The contribution deals with design of progressive CONWIP production control system, which is later enriched by the kanban principles of pressure.